Post-Translational Modifications of Deubiquitinating Enzymes: Expanding the Ubiquitin Code - Wang, Yanfeng; Wang, Feng (Frontiers in Pharmacology, 2021)
Post-translational modifications such as ubiquitination play important regulatory roles in several biological processes in eukaryotes. This process could be reversed by deubiquitinating enzymes (DUBs), which remove conjugated ubiquitin molecules from target substrates. Owing to their role as essential enzymes in regulating all ubiquitin-related processes, the abundance, localization, and catalytic activity of DUBs are tightly regulated. Dysregulation of DUBs can cause dramatic physiological consequences and a variety of disorders such as cancer, and neurodegenerative and inflammatory diseases. Multiple factors, such as transcription and translation of associated genes, and the presence of accessory domains, binding proteins, and inhibitors have been implicated in several aspects of DUB regulation. Beyond this level of regulation, emerging studies show that the function of DUBs can be regulated by a variety of post-translational modifications, which significantly affect the abundance, localization, and catalytic activity of DUBs. The most extensively studied post-translational modification of DUBs is phosphorylation. Besides phosphorylation, ubiquitination, SUMOylation, acetylation, oxidation, and hydroxylation are also reported in DUBs. In this review, we summarize the current knowledge on the regulatory effects of post-translational modifications of DUBs.